Expansão da rede viária na Amazônia Oriental, Rodovia Perimetral Norte, Amapá - Francinete da Silva Facundes; Ricardo Ângelo Pereira Lima; Valdenira Ferreira dos Santos (Confins)
This article deals with the multitemporal analysis of the network of roads in the Northern Perimetral Highway, Amapá State, Brazil, in order to understand the process of territorial occupation along the area. The development of the road network is analyzed on the basis of two categories of roads: official (resulting from political strategies) and endogenous (resulting from the action of private agents and possible spontaneous occupations). For the analysis, we used 12 scenes from the Landsat satellite series between 1988 and 2014, data from the road map database of the Economic Ecological Zoning Program (ZEE) and field interviews. The rate of increase of the road network was associated with socio-spatial events that influenced the expansion of that network. The results allowed us to determine that the main actors responsible for the process of expansion of the official road network were the projects of the INCRA settlements, linked to the political strategies of regional occupation. The evolution of the endogenous roads resulted from the action of mineral and logging capital, activities that have been expanding in the region independent of territorial planning guidelines. The influences of these activities are important for the changes in the space of use and occupation of the territory and consequently in the processes of deforestation and development of the region.